Deciphering the Metabolic Mechanisms of Damp Retention in the Middle-Jiao Syndrome using High-throughput UPLC-Q-TOF-MS - Li, Na; Zhu, Tongyan; Chen, Jianhui; Dong, Yuxin; Zhao, Chunying; Tian, Yuxuan; Liu, Yuling; Hong, Xia; Xiong, Hui (Combinatorial Chemistry & High Throughput Screening, 2026)
<span class=
Keywords: metabolomics